EVALUASI KEPEMIMPINAN TRANSFORMASIONAL KEPALA SEKOLAH DALAM MENGEMBANGKAN E-LEARNING DI SEKOLAH LUAR BIASA - Susanti, Try; Tristianingrum, Indah; Permata, Aldes Cyntia; Naldianti, Dila (Pusat Pengembangan Pendidikan dan Penelitian Indonesia (P4I), 2025)
ABSTRACT The digital transformation in education demands adaptive and visionary school leadership, particularly in Special Needs Schools (SLB), which require specialized learning approaches. In this context, the transformational leadership of school principals plays a crucial role in promoting inclusive and sustainable e-learning development. This study aims to evaluate the transformational leadership of the principal in developing e-learning at SLB Prof. Dr. Sri Soedewi in Jambi City, specifically in relation to improving teacher performance and the effectiveness of digital learning implementation. The method used is a literature study by analyzing various relevant scientific references. The stages of analysis include collecting relevant sources based on specific keywords, categorizing literature according to the research questions, conducting content analysis on concepts and findings, and drawing conclusions through interpretation and synthesis of literature related to transformational leadership and e-learning development in SLB. The findings show that the transformational leadership of school principals significantly contributes to the development of e-learning in SLB, particularly through enhancing teacher motivation, articulating a clear vision for digitalization, and fostering a collaborative culture that supports innovation. The results also indicate that principals who apply the four dimensions of transformational leadership—idealized influence, inspirational motivation, intellectual stimulation, and individualized consideration—are able to improve teachers' readiness to integrate technology and to build an inclusive and sustainable digital learning ecosystem. Transformational leadership thus plays a strategic role in developing e-learning in SLB by reinforcing teacher motivation, conveying a digital vision, and creating an inclusive and adaptive learning environment. ABSTRAK Transformasi digital dalam dunia pendidikan menuntut kepemimpinan sekolah yang adaptif dan visioner, khususnya di Sekolah Luar Biasa (SLB) yang memiliki kebutuhan pembelajaran khusus. Dalam konteks ini, kepemimpinan transformasional kepala sekolah berperan penting dalam mendorong pengembangan e-learning yang inklusif dan berkelanjutan. Penelitian ini bertujuan untuk mengevaluasi kepemimpinan transformasional kepala sekolah dalam mengembangkan e-learning di Sekolah Luar Biasa (SLB) Prof. Dr. Sri Soedewi Kota Jambi, khususnya dalam kaitannya dengan peningkatan kinerja guru dan efektivitas implementasi pembelajaran digital. Metode yang digunakan adalah studi literatur dengan menganalisis berbagai referensi ilmiah yang relevan. ahapan analisis meliputi pengumpulan referensi relevan berdasarkan kata kunci spesifik, pengelompokan literatur sesuai rumusan masalah, analisis isi terhadap konsep dan temuan, serta penarikan kesimpulan melalui interpretasi dan sintesis literatur terkait kepemimpinan transformasional dan pengembangan e-learning di SLB. Hasil kajian menunjukkan bahwa kepemimpinan transformasional kepala sekolah berkontribusi signifikan terhadap pengembangan e-learning di SLB, terutama melalui penguatan motivasi guru, penyampaian visi digitalisasi, dan penciptaan budaya kolaboratif yang mendukung inovasi. Temuan juga mengindikasikan bahwa kepala sekolah yang menerapkan empat dimensi kepemimpinan transformasional—pengaruh ideal, motivasi inspiratif, stimulasi intelektual, dan pertimbangan individual—mampu meningkatkan kesiapan guru dalam mengintegrasikan teknologi serta membangun ekosistem pembelajaran digital yang inklusif dan berkelanjutan. Kepemimpinan transformasional kepala sekolah berperan strategis dalam mengembangkan e-learning di Sekolah Luar Biasa (SLB) melalui penguatan motivasi guru, penyampaian visi digital, dan penciptaan lingkungan pembelajaran yang inklusif dan adaptif terhadap teknologi.